Electroencephalogram-Based Motor Imagery Classification Using Deep Residual Convolutional Networks - Huang, Jing-Shan; Liu, Wan-Shan; Yao, Bin; Wang, Zhan-Xiang; Chen, Si-Fang; Sun, Wei-Fang (Frontiers in Neuroscience, 2021)
The classification of electroencephalogram (EEG) signals is of significant importance in brain computer interface (BCI) systems. Aiming to achieve intelligent classification of motor imagery EEG types with high accuracy, a classification methodology using the wavelet packet decomposition and the proposed deep residual convolutional networks (DRes-CNN) is proposed. Firstly, EEG waveforms are segmented into sub-signals. Then the EEG signal features are obtained through the wavelet packet decomposition algorithm, and some selected wavelet coefficients are retained and reconstructed into EEG signals in their respective frequency bands. Subsequently, the reconstructed EEG signals were utilized as input of the proposed deep residual convolutional networks to classify EEG signals. Finally, EEG types of motor imagination are classiﬁed by the DRes-CNN classiﬁer intelligently. The datasets from BCI Competition were used to test the performance of the proposed deep learning classifier. Classification experiments show that the average recognition accuracy of this method reaches 98.76%. The proposed method can be further applied to the BCI system of motor imagination control.